AKUNTANSI PAJAK DI TINJAU DARI LAPORAN KEUANGAN KOPERASI SYARIAH - Renny - Wulandari; Febriati Febriati (LPPM University 17 Agustus 1945 Samarinda, 2021)
Syaria accounting is not as familiar as conventional accounting for taxpayers, except for business entities whose business activities use sharia principles. Islamic accounting produces the sam financial reports as conventional accounting. As for when both accounting are used, both must make accounting reports to see how much tax is owed. However, conventional accounting strill views that the results are not in accordance with the actual condition of the company. In contrast to islamic accounting, which uses sharia principles, its said ti be the same as tax accounting, namely upholding honesty in producing reports. The results of this study show that the KSU BMT Mujahidin Islamic cooperative in the city of Pontianak which applies sharia accounting in its reporting is not tax accounting which makes it easier to report taxes, and has not reported taxes in an orderly manner. Inhibiting factors that accur are based on knowledge and tax problems with the procedures for making tax reports, lack of human resources, lack of socialization from related parties, lack of tax education and training for sharia cooperatives and understanding tax and tax accounting theory has never studied good form in form of assistance and monitoring.